Anger, Frustration, and Snitching: Inmates Describe Structured Isolation in a High-Tech Prison. Issue 9 (2nd September 2021) - Trammell, Rebecca; Rundle, Mackenzie; Borrego, Andrea R.
ABSTRACT: In this paper, we use qualitative interviews with inmates in four prisons to focus on how they describe inmate violence as it is connected to respect. We find that inmates in the one high-security and high-tech prison describe being socially isolated, frustrated, and angry. They live in fear that others will snitch on them, which leads to the punishment of solitary confinement. We argue that, in a high-tech prison, social isolation increases tension and frustration which can lead to violence. Furthermore, we link this issue to the norms of reciprocity. If respect is not bilateral, this creates a problematic environment where inmates believe they have nothing to lose. In doing so, we theoretically focus on how disrespect is directly tied to inmate violence and offer ways to reduce the tension described by these interviewees